Analisis Wacana Kritis Model Teun Van Dijk Pada Berita Online Fakta Terbaru Kasus Agus Buntung, Jumlah Terus Bertambah Hingga Jadi Sorotan DPR RI - Novi Fitriani; Afni Maikalsum (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This study aims to analyze the discourse surrounding a sexual harassment case reported on the online news portal Liputan6.com on December 7, 2024, titled “Latest Facts About the Agus Buntung Case: Increasing Number of Victims and Attention from the Indonesian Parliament (DPR RI).” The research employs a qualitative descriptive method using the critical discourse analysis model developed by Teun A. van Dijk. The subject of the study is the online news portal Liputan6.com. The data analysis technique applied is content analysis. The findings reveal that on the text dimension, three key elements are identified: text elements, social cognition elements, and social context elements. The text dimension includes macro/thematic structures addressing the theme of the news text, superstructure/schematic aspects concerning the arrangement of the news text, and microstructure covering semantic elements (background, details, intentions, presuppositions), syntactic elements (coherence, use of active sentences), stylistic elements such as lexicons, and rhetorical elements (graphics and metaphors). Active sentences dominate the text. The news dimension focuses on the sexual harassment case involving Agus Buntung, which has drawn attention from the DPR RI. Details serve as the writer's strategy to convey their stance, emphasizing public expectations for fair punishment for the legal violations committed by the perpetrator. The social cognition dimension in the analyzed text involves the cognition of journalists as news creators and society as news recipients. The journalist’s cognition is evident in the choice of words emphasizing evidence against the perpetrator and the growing number of victims. Meanwhile, the social context dimension highlights the background of the increasing number of criminal cases against women.